Possible solutions for preventing inmate sexual Assault: Examining wardens’ beliefs - Hensley, Christopher (American journal of criminal justice, 2002)
Inmate sexual assault has long been a problem within the American correctional system. Prison sex researchers have prescribed various remedies and solutions for dealing with this issue. However, few of these studies have examined wardens’ beliefs regarding possible remedies for inmate sexual assault. Using data collected from 226 wardens in 2001, this study examines the beliefs that wardens hold concerning the effectiveness of institutional policies and procedures, staff training, and increased supervision by staff on sexual assault among inmates. On average, wardens feel these possible solutions would reduce inmate sexual coercion. Multiple regression analyses reveal that race, education, percentage of inmates sexually assaulted and known by the warden, and percentage of inmates having consensual sex are statistically significant variables associated with these remedies.